A testbed for configuration management policy programming. - Van der Hoek, A.
Even though the number and variety of available configuration management systems has grown rapidly in the past few years, the need for new configuration management systems still remains. Driving this need are the emergence of situations requiring highly specialized solutions, the demand for management of artifacts other than traditional source code and the exploration of entirely new research questions in configuration management. Complicating the picture is the trend toward organizational structures that involve personnel working at physically separate sites. We have developed a testbed to support the rapid development of configuration management systems. The testbed separates configuration management repositories (i.e., the stores for versions of artifacts) from configuration management policies (i.e., the procedures, according to which the versions are manipulated) by providing a generic model of a distributed repository and an associated programmatic interface. Specific configuration management policies are programmed as unique extensions to the generic interface, while the underlying distributed repository is reused across different policies. The authors describe the repository model and its interface and present their experience in using a prototype of the testbed, called NUCM, to implement a variety of configuration management systems
Keywords: NUCM; Configuration management policy programming testbed; Configuration management repositories; Configuration management systems; Distributed configuration management; Distributed repository; Generic model; Highly specialized solutions; Organizational structures; Personnel; Physically separate sites; Programmatic interface; Version control